Performance analysis of a free-space MIMO optical wireless link over strong atmospheric turbulences - Hasan, Rokibul; Reza, Md. Lutful Hamid (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.